Security in wireless sensor networks: issues and challenges - Pathan, Al-Sakib Khan; Lee, Hyung-Woo; Hong, Choong Seon (Institute of Electrical and Electronics Engineers ( IEEE ), 2006)
Wireless Sensor Network (WSN) is an emerging technology that shows great promise for various futuristic applications both for mass public and military. The sensing technology combined with processing power and wireless communication makes it lucrative for being exploited in abundance in future. The inclusion of wireless communication technology also incurs various types of security threats. The intent of this paper is to investigate the security related issues and challenges in wireless sensor networks. We identify the security threats, review proposed security mechanisms for wireless sensor networks. We also discuss the holistic view of security for ensuring layered and robust security in wireless sensor networks.